Symptoms of Macronutrients Deficiency in Sweet Pepper (Capsicum annuum L.) - Zelia, Silva Ana; Fernando, Wamser Anderson; Hiyoshi, Nowaki Rodrigo [UNESP]; Bernardes, Cecilio Filho Arthur [UNESP]; Waldir, Mendoza-Cortez Juan (Univ Republica, Fac Agronomia, 2017)
This study aimed to describe the macronutrients deficiency symptoms and determine the leaf content of the nutrient in the appearance of the symptoms of deficiency in sweet pepper. The experiment was conducted in a greenhouse, using the Nutrient Film Technique (NFT). The treatments consisted of the omission of macronutrients in the nutrient solution, in addition to a treatment with complete nutrient solution. The foliar nutrient contents at the appearance of the symptoms of deficiency were 27.6, 0.7, 26.1, 9.6, and 1.1 g kg(-1) for nitrogen, phosphorus, potassium, calcium and magnesium. Nitrogen deficiency began with the chlorosis of the plant, followed by abortion of flowers, paralysis of apical growth, appearance of black dots and senescence of older leaves. Phosphorus deficiency began with the dark green of the leaves, followed dorsal surface of the veins became purple, abortion of flowers, curling of new leaves, growth stalling, limbo discoloration of old leaves and abscission of older leaves. Potassium deficiency began with chlorosis and necrosis of the margins of young leaves, evolving to older leaves that also presented necrosis in the interveinal region, followed by the paralysis of apical growth. Calcium deficiency symptoms were characterized by the occurrence of fruits with blossom-end rot. Magnesium deficiency symptoms were characterized by interveinal chlorosis of the middle third of the plant, progressing to the older leaves.
Keywords: Capsicum annuum L.; nutritional disorder; leaf tissue analysis